Detection of metabolites of the new synthetic cannabinoid CUMYL‐4CN‐BINACA in authentic urine samples and human liver microsomes using high‐resolution mass spectrometry. Issue 3 (24th August 2017) - Öztürk, Yeter Erol; Yeter, Oya; Öztürk, Serkan; Karakus, Goksun; Ates, Ismail; Buyuk, Yalçın; Yurdun, Turkan
Abstract: CUMYL‐4CN‐BINACA(1‐(4‐cyanobutyl)‐ N ‐(2‐phenylpropan‐2‐yl)‐1 H –indazole‐3‐carboxamide) is a recently introduced indazole‐3‐carboxamide‐type synthetic cannabinoid (SC) that was detected in herbal incense seized by of the Council of Forensic Medicine, Istanbul Narcotics Department, in May 2016 in Turkey. Recently introduced SCs are not detected in routine toxicological analysis; therefore, analytical methods to measure these compounds are in demand. The present study aims to identify urinary marker metabolites of CUMYL‐4CN‐BINACA by investigating its metabolism in human liver microsomes and to confirm the results in authentic urine samples ( n  = 80). In this study, 5 μM CUMYL‐4CN‐BINACA was incubated with human liver microsomes (HLMs) for up to 3 hours, and metabolites were identified using liquid chromatography–high‐resolution mass spectrometry (LC–HRMS). Less than 21% of the CUMYL‐4CN‐BINACA parent compound remained after 3 hours of incubation. We identified 18 metabolites that were formed via monohydroxylation, dealkylation, oxidative decyanation to aldehyde, alcohol, and carboxylic acid formation, glucuronidation or reaction combinations. CUMYL‐4CN‐BINACA N‐butanoic acid (M16) was found to be major metabolite in HLMs. In urine samples CUMYL‐4CN‐BINACA was not detected; CUMYL‐4CN‐BINACA N‐butanoic acid (M16) was major metabolite after β‐glucuronidase hydrolysis. Based on these findings, we recommend using M16 (CUMYL‐4CN‐BINACA N‐butanoic acid), M8 and M11 (hydroxylcumyl CUMYL‐4CN‐BINACA) as urinary marker metabolites to confirm CUMYL‐4CN‐BINACA intake. Abstract : CUMYL‐4CN‐BINACA was detected in herbal incense seized by of the Council of Forensic Medicine, in May 2016 in Turkey. Recently introduced SCs are not detected in routine toxicological analysis; therefore, analytical methods to measure these compounds are in demand. This study aims to identify urinary marker metabolites of CUMYL‐4CN‐BINACA by investigating its metabolism in human liver microsomes and authentic urine samples (n = 80). The study provides the first information about the metabolism of CUMYL‐4CN‐BINACA in vitro and in vivo .